Assessment Of Potable Water Supply Sources In Ilorin Metropolis, Kwara State, Nigeria - Musa, JJ; Fumen, GA (International Journal of Agricultural Research, Innovation and Technology, 2013)
Water distribution system plays a vital role in preserving and providing a desirable life quality to the public. In this regards, the reliability of supply is a major component. This study was conducted using the investigative research approach method; 5000 questionnaires which were randomly distributed round the township of Ilorin and 4658 (93.16%) were returned. Among them, 2350 respondents said that they have their own wells dugged in their respective homes, 1100 respondents had their taps running at specific periods of the week, 750 individuals said that they have boreholes available, 308 people declared that they make use of the streams and rivers running around their areas while about 150 of the remaining buy water from the water vendors so they cannot tell the exact source of the water. It was discovered that majority of the residential areas in Ilorin do not depend on the tap water supply rather they depend on dugged wells and bore holes. Int. J. Agril. Res. Innov. & Tech. 3 (1): 1-4, June, 2013 DOI: http://dx.doi.org/10.3329/ijarit.v3i1.16042